Estrategias pedagógicas y el desarrollo del lenguaje en niños de Inicial II de la escuela de Educación Básica “Azogues” período académico 2023-2024. - Correa Guarnizo, Ariana Vanessa (2024)
Pedagogical strategies are methods and techniques used by teachers to facilitate the teaching and learning process. These strategies play a crucial role in the development of language in children in early childhood education, as they encourage communication, comprehension, and the expression of thoughts and emotions. The general objective of the research is to analyze the pedagogical strategies that encourage language development in children. The aim is to identify, describe, and determine these strategies in order to provide teachers with effective tools to improve the quality of education. The methodology of the study is deductive, starting with a theoretical analysis of all the elements and then understanding their application. This method, based on logic, allows us to infer observed facts from general rules. The research approach was qualitative, allowing the application of techniques and instruments that will determine the types of instructional strategies appropriate for children in early childhood. The research was non-experimental, measuring phenomena or assumptions to analyze them without the need to manipulate variables. This study has significant potential to improve education, based on the belief that quality and warm education can prepare children to face future challenges and contribute to the development of the country. Values are a crucial component of this education, given that children spend much of their time in school. In summary, this study seeks to improve the education of children at the Azogues Basic Education School through the analysis of pedagogical strategies for language development. Its impact could extend beyond the school classrooms, contributing to the educational development of the country. Keywords: Children's rights, children's language, pedagogical strategies, language stages.